The Life Cycle of Synchytrium pogostemonis on Pogostemon cablin - DONO WAHYUNO (Indonesian Society for microbiology, 2010)
Synchytrium pogostemonis became a serious disease of patchouli cultivation in Indonesia, since it spread widely in many patchouli producing areas in Indonesia. The fungus caused warts on leaves, petioles and young stems of infected patchouli. The infected plant developed rosette habit, lost its vigour, was susceptible to drought period and finally died. Few information regarding the eco-biology and life cycle of the fungus were available The present research aimed at describing the life cycle of S. pogostemonis. The diseased patchouli was obtained through artificial inoculation. Mass inoculation was carried out by placing the healthy patchouli seedling close to diseased patchouli as source of inoculum and was watered regularly using the top head sprinkler . The infected leaves were observed both under disecting and light compound microscopes, and the existing fungal structure were recorded, described and measured. It was observed that S. pogostemonis is a long-cycle type fungus, the sexual reproduction was initiated by zoospores, followed subsequently by development of resting-structure spores, vesicles, sori, and sporangial formation.